Photocatalytic composite material based on fly ash as well as preparation method and application of photocatalytic composite material
By combining fly ash with BiVO4, BiVO4/fly ash composite photocatalytic material was prepared, which solved the problem of low catalytic efficiency of BiVO4 photocatalyst in practical applications, achieved efficient formaldehyde degradation effect, and had good stability and low cost.
Patent Information
- Application Number
- CN202411822536.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The existing BiVO4 photocatalysts have low catalytic efficiency, low surfactivity, fast photogenerated carrier recombination rate and poor stability in practical applications, which limit their wide application.
By compounding fly ash with BiVO4, BiVO4/fly ash composite photocatalytic material was prepared, and the resource utilization of fly ash and the excellent photocatalytic performance of BiVO4 were used to improve the photocatalytic performance.
The composite material exhibits excellent photocatalytic properties under visible light irradiation, can efficiently degrade harmful gases such as formaldehyde, has good stability and reusability, and significantly reduces the preparation cost.
Smart Images

Figure CN119633801A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection materials, and in particular relates to a fly ash-based photocatalytic composite material and a preparation method and application thereof. Background Art
[0002] With the acceleration of the global industrialization process, environmental pollution problems are becoming increasingly serious, especially the emission of harmful gases such as formaldehyde in indoor air pollution, which has posed a significant threat to human health. Formaldehyde is widely present in building materials, furniture, coatings and decorative materials, especially in newly renovated indoor environments, where the concentration is high. Long-term exposure to formaldehyde environment may cause health problems such as headaches, eye irritation, and difficulty breathing, and is even related to the occurrence of various cancers and chronic diseases. Therefore, the removal of formaldehyde has become an important environmental issue that needs to be solved urgently.
[0003] Fly ash is a solid waste generated by coal-fired power plants during the combustion of coal. Its main components include inorganic substances such as silicon dioxide, aluminum, and iron oxides. With the widespread operation of coal-fired power plants, the emission of fly ash has increased year by year, seriously affecting the quality of the environment. As a low-cost industrial waste, the resource utilization of fly ash has received widespread attention. By effectively recycling and utilizing fly ash, it can not only reduce environmental pollution, but also save resources and promote sustainable development. Therefore, the green treatment and resource utilization of fly ash has become an important research direction in the field of environmental protection.
[0004] As a green, environmentally friendly and pollution-free purification technology, photocatalytic technology is widely used in air purification, water treatment and degradation of organic pollutants, especially in indoor air treatment. Bismuth vanadate (BiVO4) has become one of the research hotspots in recent years due to its high photocatalytic activity, especially its excellent catalytic performance in the visible light region. However, the catalytic efficiency of BiVO4 photocatalysts in practical applications is usually restricted by problems such as low surface activity, fast recombination rate of photogenerated carriers and poor stability, which limits its wide application. Therefore, the development of effective modification technology or composite materials to improve the photocatalytic performance of BiVO4 has become the focus of current research in the field of photocatalysis. Summary of the invention
[0005] The present invention provides a fly ash-based photocatalytic composite material, a preparation method and application thereof, aiming to compound fly ash with BiVO4 to prepare a composite material with high-efficiency photocatalytic performance, especially in the photocatalytic degradation of organic pollutants, especially in the degradation of harmful gases such as indoor formaldehyde, showing excellent performance. With the acceleration of urbanization, the amount of fly ash generated is increasing. Recycling waste resources can not only reduce the environmental burden, but also provide cheap raw materials for the development of new materials. The present invention successfully prepares a low-cost and efficient photocatalytic composite material by using fly ash, a cheap resource material, and combining it with the excellent photocatalytic performance of BiVO4.
[0006] The composite material has excellent photocatalytic performance, can efficiently degrade organic pollutants such as formaldehyde under visible light irradiation, and has good stability and reusability. Compared with traditional photocatalytic materials, the present invention not only significantly reduces the preparation cost, but also realizes the resource utilization of waste fly ash, which has important environmental significance and application value. The composite material is particularly suitable for indoor air purification, wastewater treatment and a wide range of environmental pollution control fields.
[0007] The invention provides a fly ash-based photocatalytic composite material, which, as a photocatalytic degradation material, has the advantages of low cost, high photocatalytic performance, good stability and the like.
[0008] A fly ash-based photocatalytic composite material, the preparation method of which comprises the following steps:
[0009] (1) Pre-treating fly ash to remove unburned carbon impurities;
[0010] (2) Bi(NO3)3·5H2O and NH4VO3 are dispersed in nitric acid and deionized water respectively, and stirred evenly. Then, fly ash is added to the Bi(NO3)3·5H2O solution under stirring. After the solution is continuously stirred, the evenly stirred NH4VO3 solution is added, and then the NH3·H2O solution is added to undergo a hydrothermal reaction. The obtained product is centrifuged and dried to obtain a BiVO4 / fly ash composite photocatalytic material.
[0011] Preferably, the above-mentioned fly ash-based photocatalytic composite material is characterized in that, in step (1), the pretreatment method described in step (1) is to calcine the fly ash at 400-800° C. for 1-4 hours.
[0012] Preferably, the above-mentioned fly ash-based photocatalytic composite material is characterized in that, in step (2), under the water bath heating conditions, the temperature of the stirring pot is 25 to 65° C., and the stirring time is 2 to 6 hours.
[0013] Preferably, the above-mentioned fly ash-based photocatalytic composite material is characterized in that, in step (2), the addition of the NH3·H2O solution is to adjust the pH value of the mixed solution to 5-9 and ensure the smooth progress of the hydrothermal reaction.
[0014] Preferably, the above-mentioned fly ash-based photocatalytic composite material is characterized in that, in step (2), the hydrothermal reaction temperature is 160-200° C., and the hydrothermal time is 8-16 hours.
[0015] Preferably, the above-mentioned fly ash-based photocatalytic composite material is characterized in that, in step (2), the drying is performed at a temperature of 60 to 100° C. and the drying time is 8 to 12 hours.
[0016] Preferably, the above-mentioned fly ash-based photocatalytic composite material and its preparation method and application are characterized in that the fly ash-based photocatalytic composite material is applied in the field of photocatalytic degradation of pollution.
[0017] Preferably, the above application uses formaldehyde as the target pollutant to evaluate the photocatalytic performance of the catalyst, using a 300W xenon lamp and a 400nm cut-off filter as a visible light source in a 50mL closed stainless steel gas phase reactor, and the formaldehyde gas is composed of a 37% formaldehyde solution (0.16mg·L -1 )generate.
[0018] The above application method is as follows: 100 mg of photocatalytic material is evenly spread on the glass surface in the reactor, and 0.02 mL of formaldehyde solution is dripped into a vial in the reactor. The reactor is sealed and the formaldehyde solution is heated and evaporated within 30 minutes using an infrared lamp to ensure the generation of formaldehyde gas. After turning off the infrared lamp, the water cooling system is started for temperature control, and a dark reaction is performed for 30 minutes to establish the adsorption equilibrium of formaldehyde on the catalyst surface. The xenon lamp is turned on and the photocatalytic reaction is started. During the reaction, a gas sample is collected every 5 minutes. The formaldehyde concentration of the gas sample is determined by a UV-visible spectrophotometer, and ammonium ferrous sulfate and phenol reagent are used to react with the collected gas sample to generate a blue compound with a peak absorbance at 630 nm. The degradation effect of formaldehyde is calculated by measuring the absorbance of the blue compound.
[0019] Beneficial effects:
[0020] The fly ash-based photocatalytic composite material and the preparation method thereof provided by the present invention have significant economic and environmental benefits. As a cheap industrial waste, the resource utilization of fly ash not only helps to reduce environmental pollution, but also can significantly reduce the preparation cost of photocatalytic materials. By compounding fly ash with BiVO4, the prepared photocatalytic composite material exhibits excellent photocatalytic performance under visible light irradiation, can efficiently degrade harmful gases such as formaldehyde, effectively improve indoor air quality, and protect human health. The composite material also has good stability and reusability, and can still maintain a high catalytic activity after long-term use, reducing the frequency of material replacement and reducing the cost of use.
[0021] In addition, the preparation method of the present invention is simple and easy to implement, and can efficiently prepare photocatalytic composite materials under relatively mild conditions, which meets the requirements of green environmental protection. The low energy consumption characteristics of the method, combined with the resource utilization of fly ash, not only promote the reuse of waste, but also meet the concept of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a degradation effect diagram of a fly ash-based photocatalytic composite material prepared in Examples 1 to 5 of the present invention;
[0023] Figure 2 The XRD spectrum of a fly ash-based photocatalytic composite material prepared in Examples 1 to 5 of the present invention;
[0024] Figure 3 The Raman spectrum of a fly ash-based photocatalytic composite material prepared in Examples 1 to 5 of the present invention;
[0025] Figure 4 This is a test chart of the cyclic stability of the composite photocatalytic material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0026] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0027] Example 1
[0028] A fly ash-based photocatalytic composite material (BiVO4 to fly ash mass ratio 1:4), comprising the following steps:
[0029] Step 1: Put the fly ash into a crucible and place it in a muffle furnace, and calcine it at 600°C for 2.5h.
[0030] Step 2: Dissolve 0.97g Bi(NO3)3·5H2O and 0.234g NH4VO3 in 50mL nitric acid and deionized water respectively, and stir until completely dissolved. Under continuous stirring, slowly add 2.592g fly ash to the Bi(NO3)3·5H2O solution and continue stirring. After adding NH4VO3 solution and stirring evenly, use NH3·H2O to adjust the pH value of the solution to 7. After stirring evenly, transfer the mixed solution to a 150mL reactor and place it in an oven at 180℃ for 12h of hydrothermal reaction. After the reaction is completed, collect the precipitate, wash it repeatedly with ethanol and deionized water, and separate it using a centrifuge. The washed product is dried at 80℃ to obtain a BiVO4 / fly ash composite photocatalytic material.
[0031] Step 3: To evaluate the photocatalytic performance of the catalyst, 100 mg of photocatalytic material was evenly spread on the glass surface in the reactor, and 0.02 mL of formaldehyde solution was dripped into the vial in the reactor. The reactor was sealed and the formaldehyde solution was heated and evaporated within 30 minutes using an infrared lamp to ensure the generation of formaldehyde gas. After turning off the infrared lamp, the water cooling system was started for temperature control, and a dark reaction was performed for 30 minutes to establish the adsorption equilibrium of formaldehyde on the catalyst surface. The xenon lamp was turned on for photocatalytic reaction, and gas samples were collected every 5 minutes during the reaction. The formaldehyde concentration of the gas sample was determined by a UV-visible spectrophotometer, and ammonium ferrous sulfate and phenol reagent were used to react with the collected gas sample to generate a blue compound with a peak absorbance at 630 nm. The degradation effect of formaldehyde was calculated by measuring the absorbance of the blue compound.
[0032] Example 2
[0033] A fly ash-based photocatalytic composite material (BiVO4 to fly ash mass ratio 1:2), comprising the following steps:
[0034] Step 1: Put the fly ash into a crucible and place it in a muffle furnace, and calcine it at 600°C for 2.5h.
[0035] Step 2: Dissolve 1.94g Bi(NO3)3·5H2O and 0.468g NH4VO3 in 50mL nitric acid and deionized water respectively, and stir until completely dissolved. Under continuous stirring, slowly add 2.592g fly ash to the Bi(NO3)3·5H2O solution and continue stirring. After adding the NH4VO3 solution and stirring evenly, use NH3·H2O to adjust the pH value of the solution to 7. After stirring evenly, transfer the mixed solution to a 150mL reactor and place it in an oven at 180°C for 12h of hydrothermal reaction. After the reaction is completed, collect the precipitate, wash it repeatedly with ethanol and deionized water, and separate it using a centrifuge. The washed product is dried at 80°C to obtain a BiVO4 / fly ash composite photocatalytic material.
[0036] Step 3: To evaluate the photocatalytic performance of the catalyst, 100 mg of photocatalytic material was evenly spread on the glass surface in the reactor, and 0.02 mL of formaldehyde solution was dripped into the vial in the reactor. The reactor was sealed and the formaldehyde solution was heated and evaporated within 30 minutes using an infrared lamp to ensure the generation of formaldehyde gas. After turning off the infrared lamp, the water cooling system was started for temperature control, and a dark reaction was performed for 30 minutes to establish the adsorption equilibrium of formaldehyde on the catalyst surface. The xenon lamp was turned on for photocatalytic reaction, and gas samples were collected every 5 minutes during the reaction. The formaldehyde concentration of the gas sample was determined by a UV-visible spectrophotometer, and ammonium ferrous sulfate and phenol reagent were used to react with the collected gas sample to generate a blue compound with a peak absorbance at 630 nm. The degradation effect of formaldehyde was calculated by measuring the absorbance of the blue compound.
[0037] Example 3
[0038] A fly ash-based photocatalytic composite material (BiVO4 to fly ash mass ratio 1:1), comprising the following steps:
[0039] Step 1: Put the fly ash into a crucible and place it in a muffle furnace, and calcine it at 600°C for 2.5h.
[0040] Step 2: Dissolve 1.94g Bi(NO3)3·5H2O and 0.468g NH4VO3 in 50mL nitric acid and deionized water respectively, and stir until completely dissolved. Under continuous stirring, slowly add 1.296g fly ash to the Bi(NO3)3·5H2O solution and continue stirring. After adding the NH4VO3 solution and stirring evenly, use NH3·H2O to adjust the pH value of the solution to 7. After stirring evenly, transfer the mixed solution to a 150mL reactor and place it in an oven at 180°C for 12h of hydrothermal reaction. After the reaction is completed, collect the precipitate, wash it repeatedly with ethanol and deionized water, and separate it using a centrifuge. The washed product is dried at 80°C to obtain a BiVO4 / fly ash composite photocatalytic material.
[0041] Step 3: To evaluate the photocatalytic performance of the catalyst, 100 mg of photocatalytic material was evenly spread on the glass surface in the reactor, and 0.02 mL of formaldehyde solution was dripped into the vial in the reactor. The reactor was sealed and the formaldehyde solution was heated and evaporated within 30 minutes using an infrared lamp to ensure the generation of formaldehyde gas. After turning off the infrared lamp, the water cooling system was started for temperature control, and a dark reaction was performed for 30 minutes to establish the adsorption equilibrium of formaldehyde on the catalyst surface. The xenon lamp was turned on for photocatalytic reaction, and gas samples were collected every 5 minutes during the reaction. The formaldehyde concentration of the gas sample was determined by a UV-visible spectrophotometer, and ammonium ferrous sulfate and phenol reagent were used to react with the collected gas sample to generate a blue compound with a peak absorbance at 630 nm. The degradation effect of formaldehyde was calculated by measuring the absorbance of the blue compound.
[0042] Example 4
[0043] A fly ash-based photocatalytic composite material (BiVO4 to fly ash mass ratio 2:1), comprising the following steps:
[0044] Step 1: Put the fly ash into a crucible and place it in a muffle furnace, and calcine it at 600°C for 2.5h.
[0045] Step 2: Dissolve 1.94g Bi(NO3)3·5H2O and 0.468g NH4VO3 in 50mL nitric acid and deionized water respectively, and stir until completely dissolved. Under continuous stirring, slowly add 0.648g fly ash to the Bi(NO3)3·5H2O solution and continue stirring. After adding the NH4VO3 solution and stirring evenly, use NH3·H2O to adjust the pH value of the solution to 7. After stirring evenly, transfer the mixed solution to a 150mL reactor and place it in an oven at 180°C for 12h of hydrothermal reaction. After the reaction is completed, collect the precipitate, wash it repeatedly with ethanol and deionized water, and separate it using a centrifuge. The washed product is dried at 80°C to obtain a BiVO4 / fly ash composite photocatalytic material.
[0046] Step 3: To evaluate the photocatalytic performance of the catalyst, 100 mg of photocatalytic material was evenly spread on the glass surface in the reactor, and 0.02 mL of formaldehyde solution was dripped into the vial in the reactor. The reactor was sealed and the formaldehyde solution was heated and evaporated within 30 minutes using an infrared lamp to ensure the generation of formaldehyde gas. After turning off the infrared lamp, the water cooling system was started for temperature control, and a dark reaction was performed for 30 minutes to establish the adsorption equilibrium of formaldehyde on the catalyst surface. The xenon lamp was turned on for photocatalytic reaction, and gas samples were collected every 5 minutes during the reaction. The formaldehyde concentration of the gas sample was determined by a UV-visible spectrophotometer, and ammonium ferrous sulfate and phenol reagent were used to react with the collected gas sample to generate a blue compound with a peak absorbance at 630 nm. The degradation effect of formaldehyde was calculated by measuring the absorbance of the blue compound.
[0047] Example 5
[0048] A fly ash-based photocatalytic composite material (BiVO4 to fly ash mass ratio 4:1), comprising the following steps:
[0049] Step 1: Put the fly ash into a crucible and place it in a muffle furnace, and calcine it at 600°C for 2.5h.
[0050] Step 2: Dissolve 1.94g Bi(NO3)3·5H2O and 0.468g NH4VO3 in 50mL nitric acid and deionized water respectively, and stir until completely dissolved. Under continuous stirring, slowly add 0.324g fly ash to the Bi(NO3)3·5H2O solution and continue stirring. After adding NH4VO3 solution and stirring evenly, use NH3·H2O to adjust the pH value of the solution to 7. After stirring evenly, transfer the mixed solution to a 150mL reactor and place it in an oven at 180℃ for 12h of hydrothermal reaction. After the reaction is completed, collect the precipitate, wash it repeatedly with ethanol and deionized water, and separate it using a centrifuge. The washed product is dried at 80℃ to obtain a BiVO4 / fly ash composite photocatalytic material.
[0051] Step 3: To evaluate the photocatalytic performance of the catalyst, 100 mg of photocatalytic material was evenly spread on the glass surface in the reactor, and 0.02 mL of formaldehyde solution was dripped into the vial in the reactor. The reactor was sealed and the formaldehyde solution was heated and evaporated within 30 minutes using an infrared lamp to ensure the generation of formaldehyde gas. After turning off the infrared lamp, the water cooling system was started for temperature control, and a dark reaction was performed for 30 minutes to establish the adsorption equilibrium of formaldehyde on the catalyst surface. The xenon lamp was turned on for photocatalytic reaction, and gas samples were collected every 5 minutes during the reaction. The formaldehyde concentration of the gas sample was determined by a UV-visible spectrophotometer, and ammonium ferrous sulfate and phenol reagent were used to react with the collected gas sample to generate a blue compound with a peak absorbance at 630 nm. The degradation effect of formaldehyde was calculated by measuring the absorbance of the blue compound.
[0052] The present invention will be further described below in conjunction with the accompanying drawings and Examples 1 to 5:
[0053] Figure 1 The results show the effect of the fly ash-based photocatalytic composite material prepared in Examples 1 to 5 of the present invention in photocatalytic degradation of formaldehyde. Under visible light irradiation conditions, the degradation rates of Examples 1 to 5 reached 68.11%, 69.68%, 66.98%, 63.97% and 59.57%, respectively, and it can be seen that Example 2 has the best degradation effect.
[0054] Figure 2 The XRD spectrum of the fly ash-based photocatalytic composite material prepared in Examples 1 to 5 of the present invention. The spectrum provides the crystal structure information of the material and can be used to analyze the phase composition and crystallinity of the composite material. In the spectrum, multiple diffraction peaks appear at positions such as 28.7°, 31.1°, 36.7°, 40.3°, and 45.6°, which correspond to the characteristic peaks of the main crystal planes (110), (200), (211), and (220) of BiVO4, indicating that the synthesized BiVO4 has a high degree of crystallinity and no obvious impurity phase is observed. At the same time, within the range of 20° to 30° at a 2θ angle, the spectrum shows the diffraction peaks of the main crystalline phases in the fly ash, such as components such as silica and aluminate. This shows that the fly ash maintains its inherent mineral characteristics during the composite process.
[0055] Figure 3 The Raman spectra of a fly ash-based photocatalytic composite material prepared in Examples 1 to 5 of the present invention are shown in Figure 1. The prepared photocatalytic composite material has high stability in crystal structure, and the fly ash and BiVO4 are effectively combined to form a stable composite.
[0056] Figure 4This is a cyclic stability test chart of a fly ash-based photocatalytic composite material prepared in Example 2 of the present invention. The results show that the test sample has very excellent stability.
[0057] In summary, the fly ash-based photocatalytic composite material prepared in this embodiment has excellent photocatalytic degradation performance of pollutants.
[0058] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a photocatalytic composite material, characterized in that: The following steps are involved: The nitric acid dispersion of Bi(NO3)3·5H2O, the deionized water dispersion of NH4VO3, the NH3·H2O solution and fly ash are mixed, subjected to hydrothermal reaction, centrifuged and dried to obtain the BiVO4 / fly ash composite photocatalytic material.
2. The preparation method according to claim 1, characterized in that: Before the mixing, the fly ash is pre-treated to remove unburned carbon impurities therein.
3. The preparation method according to claim 2, characterized in that: The pretreatment includes calcining the fly ash at 400-800° C. for 1-4 hours.
4. The preparation method according to claim 1, characterized in that: The mixing comprises adding the fly ash to a nitric acid dispersion of Bi(NO3)3·5H2O under stirring conditions, adding a deionized water dispersion of NH4VO3 after continuous stirring, and then adding an NH3·H2O solution.
5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150-200° C. and the time is 12-24 hours.
6. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 60-100° C. and the drying time is 12-16 hours.
7. A fly ash-based photocatalytic composite material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the BiVO4 / fly ash composite photocatalytic material according to claim 7 in photocatalytic degradation of pollutants.
9. The use according to claim 8, characterized in that: The pollutant is formaldehyde.
10. A method for photocatalytic degradation of formaldehyde, characterized in that: The method comprises utilizing the BiVO4 / fly ash composite photocatalytic material as claimed in claim 7 to contact the target object under light conditions.
Citation Information
Patent Citations
Method for preparing photocatalytic material of titanium oxide immobilized on fly ash
CN101564685A
Floating type BiVO4 / floating bead composite photocatalyst and preparation method and application thereof
CN102861567A
Coal ash microsphere loaded one-dimensional nanometer titanium dioxide (TiO2) composite photocatalyst and preparation method thereof
CN102872846A
Photocatalytic composite material taking coal ash hollow microspheres as substrate and preparation method of photocatalytic composite material
CN103386309A
Floating visible-light-induced photocatalyst, and preparation method and application thereof
CN106607063A
Cited By
Multivalent bimetallic oxide ceramic catalyst as well as preparation method and application thereof
CN121648937A